PERSEPSI MASYARAKAT TERHADAP NILAI SAKRAL ALUN-ALUN LAMONGAN - M. Imam Zarkasyi Abdillah; Muhammad Choirul Mustofa; Sophie Priyanka Ardhaneswari; Hammam Rofiqi Agustapraja (BUANA SAINS, 2022)
Lamongan square (Aloon- aloon) is one of the cultural forms in the form of urban structure, especially in Java, the sacred value of the square is as a symbol of the king's power over a region and its people as a form of unification of the micro cosmos and macro cosmos that runs harmoniously, besides the function of the square as a place for religious rituals, a place for military performances and instruments in practicing the sacred power of the ruler. Along with the development and construction of the square, it affects changes in the function and value of the place. The purpose of this study was to determine the public's perception of the sacred of Lamongan Square, the data obtained from the questionnaire and analyzed using an analytical method based on the criteria for the percentage of the actual score with the ideal score. The results of the analysis of this study are the public perception of the square shows a decrease in meaning, from the sacred meaning to the meaning of public space that functions as a means of recreation and relaxation.